Ecclesial Synodality: (Importance, problems, suggestions) - González Faus, José Ignacio (Razón y fe, 2021)
Synodality means walking together. If the Church is communion in being, it must also be communion in acting. But just because something is indispensable does not mean that it is easy. The article examines the difficulties and dangers that can threaten the indispensable ecclesial synodality, and seeks criteria for discernment in order to face these difficulties, drawing on enlightened examples from the history of the Church. Because, as Cardinal Carlos Aguiar said, it is a matter of “listening to the whole people of God, excluding no one”.